2019
DOI: 10.1002/adfm.201905805
|View full text |Cite
|
Sign up to set email alerts
|

The Biomolecular Corona in 2D and Reverse: Patterning Metal–Phenolic Networks on Proteins, Lipids, Nucleic Acids, Polysaccharides, and Fingerprints

Abstract: The adsorption of biomolecules onto nanomaterials can alter the performance of the nanomaterials in vitro and in vivo. Recent studies have primarily focused on the protein "corona", formed upon adsorption of proteins onto nanoparticles in biological fluids, which can change the biological fate of the nanoparticles. Conversely, interactions between nanomaterials and other classes of bio molecules namely, lipids, nucleic acids, and polysaccharides have received less attention despite their important roles in bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…We recently developed a protocol for visualizing latent fingerprints (i.e., invisible residual biomolecule patterns) through the formation of Ag nanoparticles on pre-formed MPN films patterned by biomolecules (Figure 6f). 56 (Figure 7a). 58 These polymeric polyphenols then assembled into microspheres with a diameter of 1-3 μm and exhibited green fluorescence under UV irradiation (Figure 7b and 7c).…”
Section: Metal Coordinationmentioning
confidence: 99%
“…We recently developed a protocol for visualizing latent fingerprints (i.e., invisible residual biomolecule patterns) through the formation of Ag nanoparticles on pre-formed MPN films patterned by biomolecules (Figure 6f). 56 (Figure 7a). 58 These polymeric polyphenols then assembled into microspheres with a diameter of 1-3 μm and exhibited green fluorescence under UV irradiation (Figure 7b and 7c).…”
Section: Metal Coordinationmentioning
confidence: 99%
“…33 In a different study, Yun et al developed a planarsubstrate based protocol in order to investigate the interaction of metal-phenolic network (MPN)-based nanomaterials with multiple biomolecules including synthetic single stranded 40 bp DNA fragments. 31 It is important to note however, that these DNA molecules do not reflect the size and structure of endogenous plasma cfDNA, nor the molecular complexity of blood. 31 Despite the above-mentioned preliminary indications of the interaction of nucleic acids with the surface of NPs, no studies have demonstrated the presence of cfDNA in the biomolecule corona formed when NPs come into contact with human plasma.…”
Section: Discussionmentioning
confidence: 99%
“…31 It is important to note however, that these DNA molecules do not reflect the size and structure of endogenous plasma cfDNA, nor the molecular complexity of blood. 31 Despite the above-mentioned preliminary indications of the interaction of nucleic acids with the surface of NPs, no studies have demonstrated the presence of cfDNA in the biomolecule corona formed when NPs come into contact with human plasma. The present study aimed to answer this fundamental question and establish whether cfDNA participates in the formation of the biomolecule corona in a non-specific, untargeted manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations